Associations Between Maternal Distress During Early Life Periods and Offspring Respiratory Infections and Allergic Outcomes - Lau, Hui Xing; Kee, Michelle Zhi Ling; Yap, Qai Ven; Tham, Elizabeth Huiwen; Chan, Yiong Huak; Goh, Anne Eng Neo; Teoh, Oon Hoe; Eriksson, Johan Gunnar; Godfrey, Keith M.; Gluckman, Peter D.; Chong, Yap Seng; Chan, Jerry Kok Yen; et al. (Frontiers in Pediatrics, 2022)
Background Increasing evidence suggests that maternal distress is a risk factor for development of respiratory infections and allergic diseases in the offspring. We aim to evaluate the link between maternal distress during critical periods in early life, namely the preconception, pregnancy and postnatal periods, and development of respiratory infections and allergic diseases in the offspring from the Singapore PREconception Study of long Term maternal and child Outcomes (S-PRESTO) cohort. Methods Maternal perceived distress was evaluated using validated questionnaires including Beck Depression Inventory-II (BDI-II) administered during three time periods: preconception (three months apart at four timepoints), pregnancy (during each trimester) and postnatal (3 and 6 months post-delivery). Child eczema, rhinitis and wheeze outcomes were evaluated using a modified ISAAC questionnaire at ages 3, 6, 12, and 18 months. Child allergic sensitization was determined by skin prick testing at 18 months. Results Among 332 mother-child pairs studied, higher maternal distress during preconception and pregnancy increased the risks of wheeze development in the first 18 months; for example, preconception and pregnancy BDI-II scores ≥20 were associated with increased risks of wheeze by 18 months [adjusted risk ratios 3.2 (95%CI 1.1–9.4) and 2.5 (1.0–5.9), respectively]. Emotional and practical support from family during preconception decreased the risks of offspring wheeze. No associations were observed between maternal distress and offspring eczema, rhinitis and allergic sensitization. Conclusion Maternal distress during critical early life periods was associated with offspring wheeze in the first 18 months of life. Supporting maternal mental health even before pregnancy could reduce the risk of offspring wheeze.